Effectiveness of Mindfulness Spiritual Therapy with Murottal on Fatigue Among Hemodialysis Patients - Ariyanti, Maelina; Bahtiar, Heri; Hapipah, Hapipah; Istianah, Istianah; Ernawati, Ernawati; Setiawati, Diana (Chakra Brahmanda Lentera Institute, 2026)
Background: Fatigue is one of the most prevalent and debilitating symptoms experienced by patients with chronic kidney disease (CKD) undergoing hemodialysis, adversely affecting physical functioning, psychological well-being, and quality of life. Although mindfulness-based interventions and Qur’anic recitation (murottal) have individually demonstrated beneficial effects on psychological outcomes, evidence regarding their combined application for fatigue management remains limited. This study aimed to examine changes in fatigue levels following Mindfulness Spiritual Therapy with Murottal among patients with CKD undergoing hemodialysis. Methods: This study was conducted in accordance with the Transparent Reporting of Evaluations with Nonrandomized Designs (TREND) statement using a quantitative pre-experimental one-group pretest–posttest design. The study was carried out in the Hemodialysis Unit of RSUD H. Moh. Ruslan Kota Mataram, Indonesia. Eighteen participants were recruited through purposive sampling. Mindfulness Spiritual Therapy with Murottal was administered for approximately 20 minutes per session, twice weekly for two consecutive weeks. Fatigue levels were assessed using the Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F) questionnaire. Data were analyzed using the Shapiro–Wilk test and paired sample t-test. Results: Participants were predominantly middle-aged (55.6%), male (55.6%), and had undergone hemodialysis for 1–3 years (72.2%). The mean fatigue score decreased from 27.51 ± 7.17 at baseline to 21.32 ± 5.77 following the intervention. Paired sample t-test analysis demonstrated a statistically significant difference between pretest and posttest fatigue scores (mean difference = 6.194; 95% CI: 5.181–7.208; t = 12.899; p < 0.001). Participants who received Mindfulness Spiritual Therapy with Murottal experienced lower fatigue scores following the intervention. Conclusion: Mindfulness Spiritual Therapy with Murottal may help reduce fatigue among patients undergoing hemodialysis by addressing psychological and spiritual aspects of care. However, due to the one-group pretest–posttest design, the findings should be interpreted cautiously and cannot establish causality. Further multicenter randomized controlled trials with larger samples are needed to confirm these preliminary findings.